Prohibited Press in the Central State Bookshop in 1919–1940 - Riaubienė, Arida (Knygotyra, 2021)
This article analyses the issues of collecting and storing illegal publications and those confiscated by censorship authorities in the Central State Bookshop. It describes the structure of the military and other general censorship institutions, which sent the prohibited press to the Central State Bookshop. The aim of the study is to establish the approximate date of commencement of the activities of the department that stored confiscated by censorship or illegally issued publications, and several lists of publications prohibited by censorship and transmitted by the CSB are discussed. It is worth noting that until the 1940s, libraries were also called bookshops. In 1936, after the promulgation of the Law on Public Libraries, the Central State Bookshop became the Central State Library, and its departments became state public libraries. Between 1919–1922, under the management of Eduardas Volteris, the collection and storage of illegal and censored publications at the Central State Bookshop became a matter of interest. The legal deposit was the key and constant source of acquisition of the collections of the Central State Bookshop. In 1919 and 1935, the press laws stipulated how many mandatory copies had to be delivered to county governors or simply to state institutions. However, illegal and confiscated publications were not included in the legal deposit. The main aim of the library was to collect and store all publications published in Lithuania and by Lithuanian publishers abroad. Therefore, it was important for the library to compile a complete set of the current press. To obtain prohibited titles, the library cooperated with the structural units of the Ministry of National Defense and the Ministry of the Interior responsible for the supervision of the press. In various historical periods, unequal attention was paid to the compilation of censorship-restricted press in the Central State Bookshop. Until the 1930s, there was an intensive correspondence between war censors and the Press and Societies Division of the Department of Civil Protection about sending and collecting prohibited press in the Central State Bookstore. During c. 1920–1921, illegal and confiscated publications began to be collected in a separate office called the “secret division”. In the 1940s, censorship institutions sent lists of prohibited press of various volumes to the library. After reviewing the publications on these lists, no signs of censorship could be found. Records of censorship office provenances and censorship officers were found in individual publications that were not included in the lists of prohibited books. Although the publications confiscated by censorship authorities were stored in the library of the University of Lithuania, and in the library of Vytautas Magnus University since 1930, CSB was the only library in the interwar period in which special attention was paid to the issues of collecting prohibited press. Use of the prohibited press was restricted. These titles were not open to general public; only employees of ministries and members of the Seimas could read it. The prohibited press could serve scientific research and press statistics.
Keywords: prohibited press; censorship; mandatory copy; Central State Bookshop; Independent Lithuania; Department of Civil Protection